Coding-in-Noise Deficits are Not Seen in Responses to Amplitude Modulation in Subjects with cochlear Synaptopathy Induced by a Single Noise Exposure. (21st February 2019) - Chen, Hengchao; Xing, Yazhi; Zhang, Zhen; Tao, Shan; Wang, Hui; Aiken, Steve; Yin, Shankai; Yu, Dongzhen; Wang, Jian
Highlights: Coding-in-noise deficit is not found in cochlear damage by a brief noise exposure. The null result challenges the importance of synaptopathy by such a noise exposure. Scalp response to amplitude modulation is not sensitive to cochlear synaptopathy. Abstract: Since the first report of noise-induced synaptic damage in animals without permanent threshold shifts (PTSs), the concept of noise-induced hidden hearing loss (NIHHL) has been proposed to cover the functional deficits in hearing associated with noise-induced synaptopathy. Moreover, the potential functional deficit associated with the noise-induced synaptopathy has been largely attributed to the loss of auditory nerve fibers (ANFs) with a low spontaneous spike rate (SSR). As this group of ANFs is critical for coding at suprathreshold levels and in noisy background, coding-in-noise deficit (CIND) has been considered to be main consequence of the synaptopathy. However, such deficits have not been verified after a single, brief exposure to noise without PTS. In the present study, synaptopathy was generated by such noise exposure in both mice and guinea pigs. Responses to amplitude modulation (AM) were recorded at a high sound level in combination with masking to evaluate the existence of CINDs that might be associated with loss of low-SSR ANFs. An overall reduction in response amplitude was seen in AM-evoked compound action potential (CAP). However, no such reduction was seen in the scalp-recorded envelope following response (EFR), suggesting a compensation due to increased central gain. Moreover, there was no significant difference in masking effect between the control and noise groups. The results suggest that either there is no significant CIND after the synaptopathy we created, or the AM response tested with our protocol was not sufficiently sensitive to detect such a deficit; far-field EFR is not sensitive to cochlear pathology.